The Italians - Barzini, Luigi Giorgio, 1908-1984 (New York : Bantam Books, 1965)
Examines the character and history of the Italian people
Presents a guided tour through centuries of history of Italy. This book examines Machiavelli and Mussolini, popes, pilgrims and prostitutes, cliques and conspiracies, Casanova and the crippling power of the Church. It also shows us a divided nation, injustice, ignorance, poverty and fear.